2017
DOI: 10.2217/bem-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Conduction Block in Peripheral Nerve Using Electrical Waveforms

Abstract: Introduction Electrical nerve block uses electrical waveforms to block action potential propagation. Materials & Methods Two key features that distinguish electrical nerve block from other nonelectrical means of nerve block: block occurs instantly, typically within 1 s; and block is fully and rapidly reversible (within seconds). Results Approaches for achieving electrical nerve block are reviewed, including kilohertz frequency alternating current and charge-balanced polarizing current. We conclude with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…It is known that application of both high‐frequency alternating current (AC) and direct current (DC) can block neural conduction. It has been shown that high‐frequency AC can preferentially target either larger or smaller diameter axons depending on the frequency used , whereas DC stimulation preferentially blocks large diameter and myelinated neurons first . Specificity in the electrical modulation of neurons has been boosted by using focused multipolar and tripolar stimulation methods .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that application of both high‐frequency alternating current (AC) and direct current (DC) can block neural conduction. It has been shown that high‐frequency AC can preferentially target either larger or smaller diameter axons depending on the frequency used , whereas DC stimulation preferentially blocks large diameter and myelinated neurons first . Specificity in the electrical modulation of neurons has been boosted by using focused multipolar and tripolar stimulation methods .…”
Section: Discussionmentioning
confidence: 99%
“…Methods to block propagating APs using electrical stimulation are a more recent discovery and a current topic of investigation. Many of the current methods being used or investigated can be effective include the following: Direct current (DC) block [ 3 , 4 , 5 ], kilohertz frequency alternating current block (KHFACb) [ 6 , 7 , 8 , 9 ], anodal block [ 10 , 11 , 12 ], collision block [ 13 ], and quasi-trapezoidal stimulation [ 14 , 15 , 16 , 17 ]. Although translation to clinical use is forthcoming some methods have associated drawbacks that need resolution before translation.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking the conduction of activity in peripheral nerves has the potential to alleviate disease symptoms [1][2][3][4]. Kilohertz frequency alternating current (KHFAC) stimulation is an effective method for producing a rapid, controlled, and locally-acting conduction block [4][5][6][7][8]. KHFAC nerve block is quickly reversible, and thus enables both temporal and spatial control of the target tissue with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%